Modelling analysis and optimisation of cantilever piezoelectric energy harvesters - Patel, Rupesh (2013)
Over the last decade there has been a growing increase in research in the field of vibrational energy harvesting - devices which convert ambient vibrational energy into electrical energy. The major application area for such devices is as power sources for wireless sensors, thereby replacing currently used batteries which suffer from a finite lifespan and pose environmental issues during disposal. The vast majority of designs are cantilever beams comprising of piezoelectric layers having coverage identical to the substrate layer. It is evident from the literature that rudimentary work has been performed on design optimisation, with reliable and extensive parametric studies on geometry, especially piezoelectric layer coverage, being overlooked. As a result of this, outcomes from previous research are yet to be seen in designs for practical applications.